An efficient transformation of primary halides into nitriles through palladium-catalyzed hydrogen transfer reaction1. Issue 53 (7th July 2015) - Zou, Tao; Yu, Xiaoqiang; Feng, Xiujuan; Bao, Ming
<x xml:space="preserve">Abstract</x> Two-step one-pot transformation of primary halides into the corresponding nitriles is successfully achieved under mild conditions. In this protocol, acetone functions as both a solvent and a hydrogen acceptor.